An executive authority for the UN Development System: why this is necessary and how it could work - Max-Otto Baumann (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
United Nations (UN) member states and the UN development system (UNDS) are in a familiar bind: They have problems that they've always wanted to set right but never found the energy for, and as the problems grow, so does the challenge of correcting the wrongs. For decades, member states have discussed the need to establish a system-wide executive authority at the top of the UNDS to keep it functioning. The new “2030 Agenda for Sustainable Development” makes considering this option more urgent than ever, and the current reform process presents an opportunity to finally make the UNDS “fit for purpose”. The need to reform and in some way integrate the UNDS is little disputed by member states or experts. With its 34 funds, programmes, specialized agencies and other entities, 1,432 country offices, no effective system-wide coordination and rising levels of earmarked contributions, the UNDS is on an unsustainable trend of fragmentation and “bilateralization” (that is, donors contracting UNDS entities to implement their priorities, marginalising the multilateral framework). In its current form, the UNDS can hardly be expected to play a significant role in the collective effort to transform our world. For this, the UNDS must provide integrated development solutions, acting as one. It must become more efficient, effective and professional. And it must ensure multilateral functions such as the provision of objective knowledge, coordination, long-term orientation and intellectual leadership. A system-wide executive authority is needed to run the UNDS. The core functions of such an executive authority would be to administer the Resident Coordinator system, draft and monitor a system-wide framework and corresponding financial overview, and act as the “brain” of the UNDS. How could this be implemented? This paper suggests that instead of adding new structures, the existing coordination forum of the UN Development Group (UNDG) should be separated from the UN Development Programme (UNDP) and re-organized as the executive authority: The position of the UNDG Chair should be transformed into the High Commissioner for Sustainable Development (HCSD)”, heading the new executive authority. The Development Operations Coordination Office (DOCO) should form the nucleus of the new executive authority's secretariat and draw additional units and staff from the UNDS. Funding should continue to be provided through the UNDG cost-sharing agreement, which should be significantly expanded. UNDS members of the Chief Executives Board (CEB) should make up the new executive authority's board of directors, with the HCSD representing the UNDS in the CEB. The specialized agencies should be become quasi-equal members of the UNDS, subject to the same coordination as the funds and programmes, but on the basis of an opt-out mechanism. Such an executive authority would arguably enhance UNDS performance more than any other reform, with initial costs compensated by increased efficiency. It would amount to an urgently needed investment in higher quality operational activities, winning back the trust of donors and recipients.
Keywords: 330; Regionale + globale + transnationale Governance